Surface and mechanical properties of modified porous titanium scaffold - Khodaei, Mohammad; Valanezhad, Alireza; Watanabe, Ikuya; Yousefi, Reza (Surface & coatings technology, 2017)
The bioinertness makes surface treatments essential to improve the bioactivity of porous titanium scaffold, and surface treatment might affect their mechanical properties. So finding an optimum condition lying between bioactivity and mechanical properties seems to be curial. In this research, the effect of the time of the thermal oxidation at 600°C on apatite formation and mechanical properties of the porous titanium scaffold was studied. The results of thin film X-ray diffraction and Raman spectroscopy indicated that the surface of heat treated samples up to 480min was mainly covered by rutile. Also, wettability measurement and in vitro apatite formation ability assessment indicated that hydrophilicity and apatite formation ability of titanium surface could be increased with enhancing the time of heat treatment up to 240min. While the mechanical properties of porous titanium scaffold had no significant change upon heating up to 240min, further heating caused the reduction of mechanical properties. So, due to the mechanical properties of the porous titanium scaffold, the optimum time of thermal oxidation at 600°C in atmospheric condition was 240min for the surface treatment of the porous titanium scaffold. [Display omitted] •The surface of heat treated samples at 600 °C was mainly covered by rutile.•In vitro apatite formation ability of treated titanium scaffolds was improved with increasing the time of heat treatment.•The time of heat treatment affected the mechanical properties of titanium scaffolds via varying thickness of titanium oxide.